HUBUNGAN LAMA PEMASANGAN KATETER DENGAN KEJADIAN INFEKSI SALURAN KEMIH PADA PASIEN DI RUANG PENYAKIT DALAM RUMKIT TK II DR. SOEPRAOEN MALANG - Ana, Karisma Dwi; Riwayati, Nunuk Yuli; Jayanti, Siska Febri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Urinary tract infections are included by pathogenic microorganisms associated with objects in the urinary tract. Catheter placement is one of the interventions given to patients with urinary tract disorders. This can save lives, especially if the urinary tract is blocked or if the patient is unable to make urine transfer smoothly. This study uses a correlational analytic research design using a cross sectional design.The sample of this study was a patient with a catheter in the disease room in Hospital LevelII Dr. Soepraoen as many as 38 people by using side-taking techniques with accidental sampling. The measuring instrument used was an observation sheet. The results of this study indicate that the majority of respondents experienced a catheter installation time of two days, as many as 10 respondents (26.3%), and the majority of respondents did not experience urinary tract infections as many as 36 respondents (94.7%).Spearman rail test results obtained significance values